Prophet and the art of peace - "Gibran, Kahlil" (London, 2008)
The Prophet", first published in 1923, is the story of a seer and his wisdom. The book's astonishing success turned it into a mystical and spiritual guide for themodern era and earned its author cult status.In the 1960s, Gibran was embraced by the American counterculture movement and confirmed as the pioneer of the New Age. His messages remain powerful to this day. In one of 26 chapters the prophet Almustafa likens the soul to a battlefield, in which reason and passion seem locked in warring opposition; yet it is fruitless to fight either - instead, one must become a peacemaker and love these elements before seeking to heal oneself. God rests in reason and moves in passion. Such timeless wisdom is typical Gibran. He had originally envisaged a Prophet trilogy but only the first two of these was ever published. This book presents "The Prophet and The Garden" of the Prophet, together with selections from the writer's other timeless philosophical and spiritual writings. With his uplifting inspirations Gibran, one of the most profound writers of all, presents eternal wisdom about human life and spirituality.
Keywords: Prophet